SENSITIVITY PATTERN OF MYCOBACTERIUM TUBERCULOSIS AGAINST FIVE ANTITUBERCULOSIS DRUGS - Khan, Muhammad Tariq; Hannan, Abdul; Ahmad, Manzoor (Journal of Ayub Medical College Abbottabad, 1990)
ABSTRACT: Bacterial activity of 98 strains of M. tuberculosis was conducted against major anti-tuberculosis dings, streptomycin, 1NH ethambutol, rifampicin & pyrazinamide Sixty-four isolates were isolated from newly diagnosed cases of tuberculosis who had not started taking anti tuberculosis drugs. Thirty-four strains were isolated from patients taking anti-tuberculosis drugs from more than 02 months. Therefore, this study shows both the primary as well as acquired drug resistance. In primary drug resistance 32.8% isolates were resistant to one or more drugs. The acquired drug resistance was very high; 67.6% isolates were resistant to one or more drugs.